INTEGRATIVE HEALTHCARE APPROACHES FOR CHILDREN WITH SPECIAL NEEDS: A HOLISTIC STUDY ON CHALLENGES AND SOLUTIONS - Usman Jaffer; Che Mohd Nasril Che Mohd Nassir; Mohamed Ayaaz Ahmed; Rahmah Ahmad H. Osman; Muhammad Dhiyauddin Mohd Abas; Muhammad Lutfi Ridzuan Hon; Nur Anis Suffiah Yusafawi; Nur Arifah Zahidah Baharuddin; Nur ‘Arifah Adilah Ahmad Mugni Labib (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study delves into the intricate healthcare landscape for children with special needs, shedding light on the multifarious challenges these individuals face and evaluating the effectiveness of integrative healthcare models tailored to their unique requirements. Conducted at Sekolah Kebangsaan Pendidikan Khas Kuantan, this cross-sectional qualitative analysis involved detailed surveys with 20 teachers and engaging discussions with 24 students, aiming to unravel the complexities of providing holistic care to this vulnerable population. The investigation meticulously identifies pivotal concerns such as the prevalence of behavioral issues, particularly in autistic children, who often exhibit aggressive and self-injurious behaviors, and the struggles encountered by hearing-impaired students in communication and learning. It further explores the susceptibility of these children to frequent infections due to immune system dysfunction, exacerbated by dietary imbalances and physical inactivity. The research emphasizes the indispensable role of early detection and intervention in mitigating health risks and outlines the significance of specialized supplements, medications, and rigorous oral hygiene practices in maintaining the overall well-being of these children. Additionally, the study brings to the forefront the critical impact of socioeconomic factors on healthcare access, advocating for equitable healthcare solutions. It also highlights the transformative potential of technology, including telehealth and assistive devices, in overcoming barriers to healthcare and education. Through this analysis, the study advocates for a comprehensive, integrative care approach that encompasses medical, educational, social, and psychological services, underscoring the necessity of collaborative efforts among healthcare providers, educators, and families to significantly enhance the quality of life and well-being of children with special needs.